1984
DOI: 10.1185/03007998409109572
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetics of an oral frusemide/amiloride Combination tablet

Abstract: A randomized four-way crossover study was carried out in 12 healthy volunteers to investigate the pharmacokinetics of a new oral combination of frusemide (40 mg) and amiloride (5 mg), formulated as a single tablet. The experimental design of this bioequivalence study used commercially-available 40 mg frusemide tablets and 5 mg amiloride tablets as reference drugs, administered either separately or concomitantly. From a statistical analysis of plasma levels of frusemide and amiloride, no significant differences… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1992
1992
2016
2016

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…Several studies have reported that peak plasma levels occur 4 hr after oral administration, absorption ranges from 90% to 95% of the dose and half-life ranges from 10-14 hr. [2][3][4][5] Since amiloride exhibits an extremely low therapeutic range (0.5-25 ng/mL), only a few sufficiently specific and sensitive HPLC methods for pharmacokinetic studies have been described. [6][7][8][9][10][11] The pharmacokinetics and bioavailability of amiloride in plasma and/or urine have been investigated by determining its levels by fluorometric, 12 radioactive, 13 densitofluorimetric, 14 or spectrometric 15 assays.…”
Section: Amiloridementioning
confidence: 99%
“…Several studies have reported that peak plasma levels occur 4 hr after oral administration, absorption ranges from 90% to 95% of the dose and half-life ranges from 10-14 hr. [2][3][4][5] Since amiloride exhibits an extremely low therapeutic range (0.5-25 ng/mL), only a few sufficiently specific and sensitive HPLC methods for pharmacokinetic studies have been described. [6][7][8][9][10][11] The pharmacokinetics and bioavailability of amiloride in plasma and/or urine have been investigated by determining its levels by fluorometric, 12 radioactive, 13 densitofluorimetric, 14 or spectrometric 15 assays.…”
Section: Amiloridementioning
confidence: 99%
“…5 Furthermore, this combination is more effective for long-term treatment, since FMD has rapid absorption [6][7][8][9][10] and the presence of AMD (slower absorption) increases the length of time that the therapeutic effects last. 7,[11][12][13] A considerable number of analytical methods have been reported in the literature for the simultaneous determination of AMD and FMD, including digital derivative spectrophotometry, 3 spectrophotometry with partial least squares regression, 14 high-performance liquid chromatography with uorescence 4,5 or UV 5,[15][16][17] detection, capillary isotachophoresis, 18,19 micellar liquid chromatography with uorimetric detection, 20 solid-phase extraction followed by spectrouorimetry 1,2 and gas chromatography with electron impact mass spectrometry. 21 However, most of these methods have limitations, such as high cost, low throughput, and/or the need for laborious sample pre-treatment steps prior to analysis.…”
Section: Introductionmentioning
confidence: 99%